The Effect of Inclusion into and Exclusion from SRI-KEHATI Index on Stock Return in Indonesia Stock Exchange - Lani Diana (iBuss Management, 2019)
The establishment of Indonesian Biodiversity Foundation (KEHATI) has encouraged the growth of green economy in Indonesia. Collaborated with the Indonesian Stock Exchange (IDX), KEHATI launched SRI-KEHATI Index which consists of 25 well-performed and sustainable companies with good corporate governance and concern to its environment. Hence, the companies which are listed in this index can be considered as good and sustainable companies. The index assesses its members twice annually, and might exclude its current members and include new stocks which fulfill the selection criteria. This condition encourages the researcher to find the impact of inclusion (exclusion) of companies into (from) this index toward the stock returns from 2009 to 2017.This research has collected 34 company stocks for the inclusion event and 17 company stocks for the exclusion event and analyzed using event study methodology. Event window used in this study is 11 days consisting of five days before and after the inclusion or exclusion event. The results show that the cumulative abnormal return had insignificant negative differences before and after the inclusion event. Meanwhile, cumulative abnormal return had insignificant positive differences before and after the exclusion event. Keywords: SRI-KEHATI Index, event study, cumulative abnormal return, inclusion event, exclusion event